Foreign Direct Investment (FDI), Abundance of Natural Resources, and Economic Growth - Fajrian, Muhammad Aja; Achsani, Noer Azam; Widyastutik, Widyastutik (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2023)
The impact of foreign direct investment (FDI) on the host country’s economic growth is often discussed without considering the abundance of natural resources in the host country. The present study examines the relationship between FDI and economic growth while considering the presence of natural resources. Using panel data regression with data from 124 countries, the study finds that FDI inflows are increasing significantly, with pronounced differences between countries based on their per capita income levels. The results of the panel data regression analysis show that both FDI and natural resources positively affect economic growth. However, an increase in natural resources reduces the overall impact of FDI on economic growth. This result suggests that countries should attract FDI in sectors outside of natural resources to maximize the positive effects of FDI on economic growth.JEL Classification: F43, O4, P28, P45, Q0How to Cite:Fajrian, M. A., Achsani, N. A., & Widyastutik. (2023). Foreign Direct Investment, Abundance of Natural Resources, and Economic Growth. Signifikan: Jurnal Ilmu Ekonomi, 12(1), 11-26. https://doi.org/10.15408/sjie.v12i1.29975.